PENGARUH PENERAPAN TEKNIK IDENTITAS KORPORAT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 3 LENGAYANG KABUPATEN PESISIR SELATAN - Susanti, Nita; Rahmi, Rahmi; Aima, Zulfitri (Pendidikan Matematika, 2013)
The research is dony based on studentsÂ  problem solving mathematical are low. At the first daily test on second semester in eighth graders at SMP 3 Lengayang 2012/2013. It can be seen from theÂ  percentage of is aims to know : what are studentsâ ability problem solving mathematical by using identity corporate technigue is more better than convensional technigue. the type of research is Experimental research. The date analysis technigue is used t- test and Minitab.The result of hypothesis testing (P-value) = 0,036. It mean H0 is rejected and H1Â  is acjeted it can be concluded that the studentsâ ability toward problem solving in mathematical by using identity corporate technigue is more better than conventional technigue in eight grade at SMPN 3 Lengayang.